Effect of Fenugreek on vasomotor symptoms in menopausal women: A protocol for systematic review and meta-analysis - Wu, Tingchao (Medicine (Baltimore), 2020)
BACKGROUND: Vasomotor symptoms (hot flashes or night sweats) are closely related to the impaired quality of life in menopausal women. Fenugreek is the ripe seed of Trigonella foenum graecum Linn. In China, this plant is used to relieve menopausal symptoms in women. Although recent studies have shown that fenugreek may have a good effect on the menopausal symptoms, there is no meta-analysis to systematically evaluate its efficacy in improving menopausal vasomotor symptoms. METHODS: Randomized controlled trials that met the inclusion criteria will be retrieved in 5 English online databases and 4 Chinese online databases. The primary outcomes are changes in frequency and intensity of vasomotor symptoms that measured by validated scales. The secondary outcomes will include quality of life, blood hormone parameters, blood biochemical parameters, and adverse events. Heterogeneity of data will be assessed by I(2) and Cochrane Q statistics. Sensitivity analysis and subgroup analysis will be performed to explore the sources of heterogeneity. Egger test and Begg test will be used to assess the publication bias. Finally, we will evaluate the quality of evidence by the GRADE approach. All the data statistics will be performed using the STATA 15.0 software. RESULTS: All the results of will be published in a peer-reviewed journal. CONCLUSIONS: This meta-analysis will systematically evaluate the efficacy and safety of fenugreek in the treatment of menopausal vasomotor symptoms. OSF REGISTRATION NUMBER: 10.17605/OSF.IO/3BCY8.